Дослідження геомеханічних процесів, що супроводжують перехід геологічного порушення підготовчим вибоєм - Захарова, Л.М.; Назимко, В.В.; Мерзлікін, А.В. (Фізико-технічні проблеми гірничого виробництва, 2023)
Мета досліджень полягала в уточненні геомеханіки зрушень навколо підготовчої виробки, руйнувань оточуючого масиву й динаміки навантаження на рамне кріплення при переході геологічного порушення. При цьому використовувався метод комп’ютерного моделювання у тривимірній постановці (платформа FLAC3D) й враховувався час протікання необоротних процесів зрушення масиву гірських порід та позамежне їх деформування. Результати дослідження. Вирішена задача дослідження перерозподілу напружень навколо підготовчої виробки й навантаження на її рамне кріплення під час переходу геологічного порушення. Задача вирішена у тривимірній постановці з урахуванням спільного опору рамного кріплення і деформування перерізу підготовчої виробки. Наукова новизна. Вперше доведено, що напруження навколо перерізу виробки у зоні геологічного порушення зменшуються, а необоротні зрушення, розміри зруйнованих порід й навантаження на рамне кріплення збільшуються у зоні порушення. Отримані кількісні оцінки вказаних відмінностей. Практична значимість результатів. Особливості геомеханіки переходу геологічного порушення дозволяють уточнити вимоги до параметрів кріплення підготовчих у зоні геологічного порушення. Ключові слова: деформації, напруження, перехід геологічного порушення, прохідницький вибій The purpose of the research was to clarify the geomechanics of displacements around the preparatory work, the destruction of the surrounding mass, and the dynamics of the load on the frame mount during the transition of a geological fault. At the same time, the method of computer modeling in a three-dimensional setting (FLAC3D platform) was used, taking into account the time of the irreversible processes of shifting of the rocks mass and their external deformation. Findings. Further development of the solution to the problem of the transition of a geological fault was achieved, taking into account the best achievements and achievements of domestic and foreign researchers. At the same time, the frame fastening was modeled in the form of clear frames, which were installed 1 m apart. In addition, the task was done in the mode of large deformations, when the positions of the nodes of the calculated finite-difference scheme were adjusted taking into account the obtained displacements and deformations of the rock mass. This approach significantly increases the reliability of modeling results when the transition of rocks through the strength limit is taken into account. Even more important is the direct consideration of the time of geomechanical processes, when the dynamic effects that arise in the process of displacements and especially the destruction of the host rocks are automatically modeled, and the time, and therefore the speed of advance of the preparatory works, is taken into account. Originality. For the first time, it has been proven that the stresses around the cross-section of the mine in the zone of geological fault decrease, and the irreversible displacements, the size of the destroyed rocks and the load on the frame mount in the zone of geological fault increase several times in comparison with the areas where the mine has passed through an intact mass. In an intact rock mass, the failure zone develops relatively uniformly both on the sides of the working, and in the roof and sole with some preference in the sole of the working. In the area of geological fault, the priority growth of the size of the destruction zone is noted in the side walls of the working under the conditions when the rate of penetration of the working remains constant. In the case of a forced stoppage of drilling at the very beginning of entering a geological fault, the destruction may not develop in the side walls only, but also in the roof and sole. Practical implications. At the transition area of a geological fault with an amplitude of more than 5 m and the orientation of the work normal to the line of extension of the rupture, the approach of the work to the fault from the lying side, with an angle of its fall close to 45 degrees, it is advisable to apply a multi-link frame fastening with a flexibility node in the crypt part frames At the same time, it is necessary to use a combined frame-anchor fastening with long rope anchors, and their effectiveness will be significantly increased if their previous tension is applied. Keywords: deformations, stresses, transition of a geological fault, roadway face